Proximity- and Chelation-Induced SNAr 1,4-Aromatic ortho-Substitution of ortho-Methoxyphenyl 2-Alkyl Ketones - Grelier, Gwendal; Chénard, Etienne; Büschleb, Martin; Hanessian, Stephen (Synthesis, 2015)
The direct displacement of an o-methoxy group in o-methoxyaryl ketones with aryl, alkyl, and alkenyl Grignard reagents to provide a series of o-substituted ketones is described. Application of this reaction to the synthesis of a C-methyl analogue of a cyclooxygenase inhibitor is shown. The scope and limitations are discussed.
Keywords: aromatic substitution; biaryls; Grignard reaction in aryl ketones; steric hindrance; transition-metal-free reactions